2011
DOI: 10.1007/s11192-011-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric study of the trend in articles related to eutrophication published in Science Citation Index

Abstract: A keyword analysis was applied in this work to evaluate research trends of eutrophication papers published between 1991 and 2010 in any journal of all the subject categories of the Science Citation Index compiled by Institute for Scientific Information, Philadelphia, USA. Eutrophication was used as a keyword to search parts of titles, abstracts, or keywords. The published output analysis showed that eutrophication research steadily increased over the past 20 years and the annual publication output in 2008, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
7
8
0
Order By: Relevance
“…The rest of the categories included book chapter (7) and conference paper (7). The percentages obtained were in agreement with the figures that resulted from other bibliometric studies, which reported the clear prevalence of articles over other types of publications in chemical or environmental engineering topics [74,75]. However, in this case, the higher contribution of reviews and the lower contribution of conference papers when compared to the research trends on other topics in these fields should be mentioned [42].…”
Section: Data Sources and Methodologysupporting
confidence: 90%
“…The rest of the categories included book chapter (7) and conference paper (7). The percentages obtained were in agreement with the figures that resulted from other bibliometric studies, which reported the clear prevalence of articles over other types of publications in chemical or environmental engineering topics [74,75]. However, in this case, the higher contribution of reviews and the lower contribution of conference papers when compared to the research trends on other topics in these fields should be mentioned [42].…”
Section: Data Sources and Methodologysupporting
confidence: 90%
“…These percentages were not too concordant with the figures obtained by other bibliometric studies that demonstrated the clear supremacy of articles over other types of publication in other engineering areas, such as environmental or chemical engineering [43][44][45].…”
Section: Bibliometric Analysis Of Research On Pavement Management (20supporting
confidence: 82%
“…The other nine categories represented \0.5 % in each item. This distribution pattern of documents types is similar to other bibliometric research in nutrients and eutrophication using the Web of Science database (Gao and Guo 2014;Yi and Jie 2011), which is why articles are most chosen for bibliometric analysis. Considering the representativeness and impact of publications, records from the document types of articles, reviewer, and letter were chosen as data for analysis in this study.…”
Section: Resultssupporting
confidence: 76%
“…Top 20 with the most publications was showed in Table 2, accounting for over 90 % of the total publications. It is not a surprise that the USA ranked first in terms of the number of articles, TLCS (total local citations score), and TGCS (total global citations score), which repeats itself many times in other research (Gao and Guo 2014;Ho 2013;Yi and Jie 2011). Another expected phenomenon found in this study is the absolute dominance of developed countries (countries in North America and Europe) in this top productive list.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation